Examining EFL Pre-service Teachers’ Use of Classroom Discourse Moves and Factors Affecting Their Choices - Kani, Zeynep Gülşah; Türkmen, Gökçe Nur (LPPM Universitas Advent Indonesia, 2024)
There are many factors that affect a teacher's classroom behavior. What these effects depend on, where these effects come from, and how they affect the teacher vary from teacher to teacher. This mixed-method descriptive case study aimed to examine the classroom behaviors of twelve Turkish EFL pre-service teachers at a western state university and to understand their thoughts about what the classroom discourse moves that they use depend on. With this aim, the classroom behaviors of EFL pre-service teachers were examined through observation and interviews in complementary to each other. The frequencies of selected classroom discourse moves, which are “eliciting, extending, facilitating, clarifying, supporting and omitting” were observed, and the most frequently used moves were revealed. The pre-service teachers’ opinions evident in their extracts from interviews pointed out the effect of personal and social factors on their behaviors in the classroom and their views on the classroom discourse moves. As a result of the research study, it was found that the pre-service teachers frequently used the facilitating and clarifying discourse moves, and the factor that most affected them was their prior teachers and university education.